2014
DOI: 10.4103/0972-5229.126084
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis induced thrombotic thrombocytopenic purpura

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a rare syndrome of unknown cause with an estimated incidence of one case per million. The disease is characterized by a pentad of symptoms: Thrombocytopenia, microangiopathic hemolytic anemia, neurologic changes, renal dysfunction, and fever. It causes thrombosis in the microvasculature of several organs, producing diverse manifestations. Acute pancreatitis (AP) is a well-described consequence of TTP. Acute pancreatitis triggering TTP is uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Thrombotic thrombocytopenic purpura (TTP) is a rare acquired or congenital disorder with an annual incidence of six cases per million (1). Its pathogenesis involves an imbalance between von Willebrand factor (vWF) multimers and ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrombotic thrombocytopenic purpura (TTP) is a rare acquired or congenital disorder with an annual incidence of six cases per million (1). Its pathogenesis involves an imbalance between von Willebrand factor (vWF) multimers and ADAMTS13.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology is found in only 10% of cases. It has been associated with pregnancy, vascular disease, malignancy, and certain drugs, and the newest associations are HIV and pancreatitis (1). Case reports have shown TTP-aHUS secondary to autoimmune pancreatitis, alcohol abuse, gallstones, and granulomatous pancreatic inflammation due to sarcoid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today it is recognized as a rare disorder, with an annual incidence of around 6 per million. [ 2 ] TTP has multiple and diverse etiologies, manifestations, associated conditions, and risk factors. This disease has a characteristic pentad of symptoms: microangiopathic hemolytic anemia (MAHA), neurologic changes, fever, thrombocytopenia, and renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…TTP can be congenital (deficiency of ADAMTS13) or acquired. To the best of our knowledge, there are only a few case reports published describing the rare phenomenon of TTP induced by pancreatitis [ 2 , 4 – 10 ]. Swisher [ 9 ] reported that the expected incidence of coincidental occurrence of TTP and pancreatitis in the same year is 3.75 per 10 9 population.…”
Section: Introductionmentioning
confidence: 99%